Problems of the impact of the sanctions on export and import in Russia - V. A. Kardanov; T. A. Petrova (Вестник университета, 2023)
The article studies the problems and prospects of the domestic economy development. An overview of exports and imports of the Russian Federation by goods and countries in 2022–2023 has been presented. The study considers the degree of development of the issues concerning mitigation of the consequences of economic sanctions imposed by the Western countries and some of the international organizations on the Russian economy. The restrictions that have been adopted by both sides may well lead not only to domestic complications in Russia, but also to a global worldwide crisis. The article concludes that the government agencies’ role in eliminating the problems that have arisen as a result of economic sanctions is significant. Under the prevailing conditions, further strengthening of cooperation between Russia, China, Turkey, and India, as well as other states in the near and far abroad states that have not participated in the anti-Russian sanctions, seems to lead to minimization of economic and logistical losses.